Determining the prevalence of vestibular screening failures in pediatric cancer patients whose therapies include radiation to the head/neck and platin‐based therapies: A pilot study. Issue 6 (30th January 2018) - Camet, Miranda L.; Hayashi, Susan S.; Sinks, Belinda C.; Henry, Jennifer; Gettinger, Katie; Hite, Ashley; Kiefer, Juliann; Mohrmann, Caroline; Sandheinrich, Taryn; Gao, Feng; Hayashi, Robert J.
Abstract: Background: Sensorineural hearing loss due to ototoxic cancer therapy is well established; effects on the vestibular system are unknown. We examined the feasibility of implementing vestibular screens for pediatric cancer survivors exposed to ototoxic agents. The prevalence of screening failures is reported. Methods: Cancer survivors who were 6–17 years, at least 1‐month posttreatment, and received ototoxic therapy (radiation to the head/neck, cisplatin, carboplatin) were eligible. Screening measures included (1) Pediatric Vestibular Symptom Questionnaire, (2) Modified Clinical Test of Sensory Interaction on Balance, and (3) Dynamic Visual Acuity. Results: Vestibular screening failures were observed in 30 participants (60%). Patients with a brain tumor diagnosis were at increased risk for failures compared to nonbrain tumor patients (74.2% vs. 36.8%, P = 0.009). Patients who underwent brain surgery were at increased risk for failures compared to patients without brain surgery (71% vs. 42%, P = 0.043). Patients with a longer duration between end of treatment and vestibular screening had a reduced risk of failures, with an almost 20% decrease for each year between the time points (odds ratio = 0.812; 95% confidence interval: 0.683–0.964, P = 0.018). Receiving carboplatin correlated with a decreased risk of failure ( P = 0.016), due to a negative correlation with other clinical risk factors (diagnosis of a brain tumor, major brain surgery) that are associated with vestibular screening failure. Conclusion: Vestibular screening failures are highly prevalent in childhood cancer survivors who received ototoxic therapy. Broad screening of this population and further characterization of these patients are warranted.